Entero-pleural fistula as a long-term complication of patch repair for congenital diaphragmatic hernia - Yota Suzuki; Taylor Williams; Ravi S. Radhakrishnan (Elsevier, 2021)
For patients with large congenital diaphragmatic hernias (CDH), a mesh patch repair is currently accepted as a safe and feasible surgical option. As the survival rate of CDH has improved over time, the long-term sequelae of CDH warrant further detailed examination. Herein, we report a case of an entero-pleural fistula as a long-term complication of diaphragmatic hernia repair with synthetic mesh. Long-term complications of diaphragmatic hernia patch repairs remain sparse in the literature.